2008
DOI: 10.1007/s10661-008-0536-7
|View full text |Cite
|
Sign up to set email alerts
|

Benthic communities of streams related to different land uses in a hydrographic basin in southern Brazil

Abstract: Different land uses affect the characteristics of a hydrographic basin, reflected in the river water quality, and consequently affecting the aquatic biota. The benthic community closely reflects the alterations caused by different human activities. In this study, the effects of different land uses were evaluated by analysis of the benthic community structure in streams with urban, agricultural and pasturage influences, as well as areas in better-conserved regions. The abiotic parameters showed distinct seasona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
43
0
11

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(57 citation statements)
references
References 33 publications
(66 reference statements)
3
43
0
11
Order By: Relevance
“…High densities of Oligochaeta and Chironomidae are indicative of high levels of organic matter (Lang, 1998;Hepp and Santos, 2009), as these benthic invertebrates are more tolerant to pollution (Bubinas and Jagminiené, 2001). Our data showed that these groups presented greater relative abundances in sites near the cages, with an increased total number of individuals.…”
Section: Discussionmentioning
confidence: 56%
“…High densities of Oligochaeta and Chironomidae are indicative of high levels of organic matter (Lang, 1998;Hepp and Santos, 2009), as these benthic invertebrates are more tolerant to pollution (Bubinas and Jagminiené, 2001). Our data showed that these groups presented greater relative abundances in sites near the cages, with an increased total number of individuals.…”
Section: Discussionmentioning
confidence: 56%
“…The core metric %MOLD was chosen as the number of Diptera and Mollusca individuals tend to increase in the assemblages in response to impacts such as increased fine sediments and high organic pollution. This phenomenon has been shown to occur in several regions in Brazil (GIOVANELLI et al 2005, HEPP & SANTOS 2009). Diversity and richness metrics of the PPPMI required identification of specimens only to family level.…”
Section: Discussionmentioning
confidence: 83%
“…However, even though studies show that some groups of EPT are tolerant, it is worth using the EPT richness to family level, once it aggregates more sensitive groups than tolerant ones and also because the family identification level used is easily achieved when compared to species and genus level. In addition, other studies showed that the number of EPT families decreased at sites with increasing impact due to disturbance (agricultural, pastures, and urban sites), possibly because of a higher nutrient concentrations (SANDIN & JOHNSON 2000, HEPP & SANTOS 2009). …”
Section: Discussionmentioning
confidence: 99%
“…Studies indicate that the adaptations of the larvae are related to biotic and abiotic factors (CORBET, 1999). Hydropsychidae can also be considered of high environmental tolerance (BUSS et al, 2002), and occurs in most studies with biomonitoring, such as Biasi et al (2008) and Hepp & Santos (2009).…”
Section: Discussionmentioning
confidence: 99%
“…TAKEDA et al, 1991;BAPTISTA et al, 2001;KIKUCHI & UIEDA, 2005;AYRES-PEREZ et al, 2006;BAL-DAN, 2006;HEPP & SANTOS, 2008;NESSIMIAN et al, 2008;RIBEIRO et al, 2009).…”
Section: Introductionunclassified